'Many hands make light work' or 'too many cooks spoil the broth'? Achieving the tricky balance of appropriate involvement in palliative care for cancer. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Porter, Katerina; Jarrett, Nikki; Addington-Hall, Julia; Corner, Jessica; Davis, Carol; Duke, Sue; Lathlean, Judith
Abstract : Background: Addressing the care needs of people with advanced cancer is often complex, requiring communication between different professional and lay care providers, across different geographical and professional boundaries. Achieving the right balance of support and autonomy can be difficult, needing to be tailored to each patient. Aim: Identify and quantify the number of people involved in the care of people with cancer and palliative care needs, and explore the network of communication pathways between these different people. Method: Case study methodology was employed, each case involving one patient and the (patient-identified) people involved in their care (PIPCs) within the past 6 months. During indepth interviews with patients (n=24; mean length 65 min) and PIPCs (n=100; mean length 30 min), respondents identified and described the network of communication pathways surrounding the patient's care. A map of each patient's care network was drawn during each interview, and was subsequently redrawn using social networking software. Results: Patients (15 female, 9 male; age range: 48–85) had a range of primary tumours (mean time since diagnosis: 9.5 months; range: 0.5–61 months). All were described as receiving or needing specialist or generalist palliative care at the time of recruitment (through General Practice (n=5); Hospital Specialist Palliative Care Team (n=8); Specialist Palliative Care Unit (n=11)). Patients identified 9–45 (mean:26) different people/teams as being involved in their care; an average of six PIPCs per case (range:0–11) were subsequently interviewed about their contribution to the communication surrounding this patient. Conclusion: Sample cases and selected communication maps are presented to illustrate the range of possibilities in numbers of PIPCs involved and the complexity of, and patient and PIPC satisfaction with, some patients' communication networks. The methodological utility of the mapping technique, and its potential contribution to achieving the right balance of involvement in palliative care, are considered.